2018
DOI: 10.1016/j.marpetgeo.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Differences between reservoirs in the intra-platform and platform margin reef-shoal complexes of the Upper Ordovician Lianglitag Formation in the Tazhong oil field, NW China, and corresponding exploration strategies

Abstract: The Upper Ordovician Lianglitag Formation in the Tazhong oil field, NW China, is dominantly composed of shallow marine carbonates, and it can be subdivided into five members lithologically. Unclear understanding of the reservoir evolution in the platform margin and intra-platform reef-shoal complexes resulted in difficulty in locating reservoirs and poor drilling success in the intra-platform. By comparing the basic characteristics, diagenesis, and porosity evolution of the two types of reservoirs, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Generally, the high-energy facies in the Ordovician period have been assumed as the basic condition for the porosity development in the ancient reservoirs [16,[22][23][24]. This agrees with the fact that high oil/gas production wells in the reef-shoal facies are much more than that in the carbonate intraplatform [8,16].…”
Section: The Production In Different Reservoirsmentioning
confidence: 58%
See 1 more Smart Citation
“…Generally, the high-energy facies in the Ordovician period have been assumed as the basic condition for the porosity development in the ancient reservoirs [16,[22][23][24]. This agrees with the fact that high oil/gas production wells in the reef-shoal facies are much more than that in the carbonate intraplatform [8,16].…”
Section: The Production In Different Reservoirsmentioning
confidence: 58%
“…The residual primary porosity is less than 0.5% in the reef-shoal reservoirs. It has beenargued that the Ordovician platform margin is favorable for the penecontemporaneous dissolution [16,[22][23][24], whereas more borehole data have shown that most reef-shoals along the Ordovician carbonate platform margins present tight reservoirs with low-porosity (<2%) and low-permeability (<0.2 mD). Further studies suggest that the high matrix porosity is related to transitional karstification by the thrust uplift in the central Tarim Basin [8,17,26].…”
Section: Discussion 41 the Production In Different Reservoirsmentioning
confidence: 99%